Application Of Sisal Fiber As A Subgrade Soil Reinforcement: In Case Of Alem Tena Town Along Modjo-Meki Express Way - Haimanot Zegeye (ASTU, 2020)
Transportation Plays A Major Role In The Development Of Economy, Industry And Society Of Any Country. Rood Construction On Poor Natural Soils Are Challenges To Geotechnical Engineers Because Such Soil Is Susceptible To Differential Settlement, Lack Of Shear Strength And Compressibility. There Are Many Techniques Used To Improve The Properties Of Poor Subgrade Soil, Use Of Natural Fiber Is Being One Of Them. Natural Fibers Are Fibers Produced From Plants Or Animals. Use Of Natural Fiber For Improving Soil Properties Is Advantageous Because They Are Cheap, Locally Available And Biodegradable, Hence They Do Not Create Disposal Problem In Environment. Sisal Fibers Are Natural Fibers Extracted From The Leaves Of Sisal Plant. The Road Construction Site??S Soil In Alem Tena Town Along Modjo-Meki Express Way Does Not Fulfill The Subgrade Soil Requirements And The Contractor Decided To Remove The Poor Soil And Infill It With Suitable Soil Which Induces Additional Cost, Contribute To The Change Of Local Geomorphology And Reduce The Conventional Natural Resource To The Next Generation. This Thesis Work Is Aimed To Investigate The Application Of Sisal Fiber As A Subgrade Soil Reinforcement. The Soil Samples Were Collected From Alem Tena Along Modjo-Meki Express Way. Two Test Pits Of Soil Samples Were Collected For The Investigation Purpose But Soil Reinforcement Was Done On Only One Test Pit. The Characterization Of Soils On Index Properties Shows That It Belongs To A-6 Class Of Soil According To Aashto Soil Classification And Cl Under Uscs. Compaction, One Point Soaked Cbr And Ucs Tests Were Conducted On Plain Soil And Soil Reinforced With Sisal Fiber. The Soil Samples Were Reinforced Randomly With Sisal Fiber In Percentages Of 0.5%, 1%, 1.5% And 2% By Dry Weight Of Soil And Length Of 10mm, 15mm And 20mm. All Sisal Fibers Were Treated By Kerosene To Reduce The Water Absorption Capacity. Water Absorption Test Shows That The Wac Of Kerosene Coated Sisal Fiber Was Decreased By 38.76% Than That Of Uncoated. Soil Samples For Cbr And Ucs Test Were Prepared At Its Mdd Corresponding To Its Omc With And Without Reinforcement. Test Results Show That Mdd Is Decreased And Omc Is Increased With Increase In Fiber Content And Length. It Was Also Observed That Increasing The Length And Content Of Sisal Fiber Further Increases The Cbr And Ucs Of Reinforced Soil And This Increase Is Substantial At Fiber Content Of 1.5% For All Fiber Lengths. The Optimum Cbr And Ucs Value Is Obtained At 1.5% Fiber Content For 15mm Fiber Length. Thus Soil Reinforcement Using Sisal Fiber Is Found To Be An Effective Improvement Technique For Poor Subgrade Soil.
Keywords: Sisal Fiber, soil reinforcement, poor subgrade